Employer-Sponsored Training in Stabilisation and Growth Policy Perspectives - Christina Håkanson; Satu Johanson; Erik Mellander (The Research Institute of Industrial Economics (IUI), 2003)
In Europe, accounting standards prevent larger expenditures on employer-sponsored training from being treated as investments. Using Sweden as example, we discuss two consequences for training. First, the timing: training will be conducted when income is large enough for training costs to be deducted without loss. This is more often possible during booms than recessions, providing a stabilisation policy dimension to training. Second, the volume: the training opportunity cost (foregone production) is largest during booms. Hence, training tends to be smaller than if conducted during downturns, possibly limiting growth.We formulate two proposals that can make training more counter-cyclical and increase the amount of training.
Keywords: D21; E32; H25; M41; M53; 330; Training; Accounting System; Timing; Growth; Zeit; Personalentwicklung; Wirkungsanalyse